Characterizing Voltage Losses in an SO2 Depolarized Electrolyzer Using Sulfonated Polybenzimidazole Membranes. Issue 14 (7th December 2017) - Garrick, Taylor R.; Wilkins, Cody H.; Pingitore, Andrew T.; Mehlhoff, Jacob; Gulledge, Alex; Benicewicz, Brian C.; Weidner, John W.
Abstract : The hybrid sulfur cycle has been investigated as a means to produce CO2 -free hydrogen efficiently on a large scale through the decomposition of H2 SO4 to SO2, O2, and H2 O, and then electrochemically oxidizing SO2 back to H2 SO4 with the cogeneration of H2 . The net effect is the production of hydrogen and oxygen from water. Recently, sulfonated polybenzimidazoles (s-PBI) have been investigated as a replacement for Nafion due to the ability to offer increased process efficiency through the generation of higher acid concentrations at lower potentials. Here, we measure the acid concentrations and individual potential contributions toward the overall operating voltage seen in the SO2 -depolarized-electrolyzer. We then determine model parameters necessary to predict voltage losses in a cell over a wide range of operating temperatures, pressures, currents and reactant flow rates.